2016
DOI: 10.1111/eie.12100
|View full text |Cite
|
Sign up to set email alerts
|

Teacher knowledge and beliefs about grammar: A case study of an English primary school

Abstract: This case study of developing teacher attitudes, beliefs and content knowledge at one primary school in the North-West of England deals with the new spelling, punctuation and grammar (SPaG) elements of the National Curriculum, focusing on grammatical terms and concepts. It uses data collected over 10 months from June 2014 to March 2015, including surveys, interviews and comments made during post-observation discussions and during SPaG CPD sessions. The findings suggest that, while much work remains to be done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…At the same time, students are now entering secondary school with a wealth of grammatical knowledge, partly as a result of the primary school Spelling, Punctuation and Grammar (SPaG)Grammar, Punctuation and Spelling (GPS) tests which were introduced in 2013, along with the substantial grammatical content on the English National Curriculum. Despite the controversies surrounding them, the tests have brought grammar 'back're-emphasised grammar to in English teaching and shown that both young children and teachers are capable of learning about (and enjoying) a wide range of grammatical concepts (see Bell 2016;Safford 2016). I see this as an opportunity for secondary school teachers to maintainbuild and build and maintain on primary school grammar knowledge, and suggest that world-based models are offer an accessible and enabling framework in with which to do so.…”
mentioning
confidence: 99%
“…At the same time, students are now entering secondary school with a wealth of grammatical knowledge, partly as a result of the primary school Spelling, Punctuation and Grammar (SPaG)Grammar, Punctuation and Spelling (GPS) tests which were introduced in 2013, along with the substantial grammatical content on the English National Curriculum. Despite the controversies surrounding them, the tests have brought grammar 'back're-emphasised grammar to in English teaching and shown that both young children and teachers are capable of learning about (and enjoying) a wide range of grammatical concepts (see Bell 2016;Safford 2016). I see this as an opportunity for secondary school teachers to maintainbuild and build and maintain on primary school grammar knowledge, and suggest that world-based models are offer an accessible and enabling framework in with which to do so.…”
mentioning
confidence: 99%
“…This makes the phenomenon of grammatical terminology and the extensive table of terms and glossary that teachers are required to teach and on which pupils are assessed significant, so much so that a meaning-oriented theorisation of grammatical terminology could be an appropriate call. Bell (2016) illustrates the difficulties in teacher-student discussion caused by lack of metalanguage, and shows that, for both teacher and child, develop control of metalanguage can help crystallise nascent insights into how language works and our understanding of it.…”
Section: Resultsmentioning
confidence: 98%
“…Comments by "Grace" cited in Watson 2015: 9-10). Most teachers in Bell's (2016) study had a largely positive perspective on, and some expressed genuine enthusiasm for, understanding and teaching grammar.…”
Section: Teachers' Perspectives On National Policymentioning
confidence: 96%
“…Safford (2016) describes an increase since 2012-13 of decontextualized grammar teaching, daily GPS lessons, lengthy test preparation and the use of past papers as teaching materials. Learning specialist terminology undoubtedly appeals to some children (Bell, 2016), but this is a poor argument for diverting time and resources to teach or test it. Debra Myhill, a contributor to the 2012-13 grammar curriculum, argues that the GPS test serves 'no valid educational purpose' (Centre for Research in Writing, 2016) and should be discontinued.…”
Section: Introductionmentioning
confidence: 99%